2011
DOI: 10.1002/jmri.22695
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion fraction of diffusion‐weighted MRI for predicting the presence of blood supply in ovarian masses

Abstract: Purpose: To evaluate whether perfusion fraction (PF) calculated with diffusion-weighted magnetic resonance imaging (MRI) predicts the presence of blood supply in ovarian masses. Materials and Methods:PFs of 92 ovarian lesions in 53 patients administered gadolinium were retrospectively calculated with diffusion-weighted images at b-values of 0, 500, and 1000 sec/mm 2 . PFs were compared between ovarian lesions, except for fat, with (n ¼ 21) or without contrast enhancement (n ¼ 57), using Student's t-test and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…In the IVIM model, D* and f are linked to perfusion, and the perfusion level may indirectly reflect the degree of tissue vascularity without the use of contrast agents . Thus, the difference of f values between type I and type II cancers we found may have implications for the use of vascular targeted therapy .…”
Section: Discussionmentioning
confidence: 89%
“…In the IVIM model, D* and f are linked to perfusion, and the perfusion level may indirectly reflect the degree of tissue vascularity without the use of contrast agents . Thus, the difference of f values between type I and type II cancers we found may have implications for the use of vascular targeted therapy .…”
Section: Discussionmentioning
confidence: 89%
“…Further prospective studies would be helpful to validate our preliminary observations regarding a potential role of ADC entropy in assisting adnexal lesion characterization. In addition, we note that recent studies have shown potential of other functional techniques such as DWI with biexponential fitting (18), MR spectroscopy (19), and quantitative dynamic contrast‐enhanced MRI (20) in adnexal lesion characterization; these techniques may also be worthwhile to pursue given the limited utility of mean ADC that was observed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…(4) was chosen to be monoexponential since this approach has been extensively used in previous IVIM analyses [1][2][3][4][5][6][7][8][9][10][11][12]. However, experiments indicating that the signal attenuation arising from blood may indeed be biexponential have been presented [21][22][23], but these studies are few and performed exclusively on rat brain.…”
Section: Discussionmentioning
confidence: 98%
“…Only a few publications exist, where the IVIM technique has been explored for retrieval of the perfusion fraction in the brain [1][2][3]. However, the IVIM concept has been more frequently applied to organs with a larger blood volume, such as the liver, pancreas, kidney, heart, placenta and ovarian masses, in both humans and animals [4][5][6][7][8][9][10][11][12]. During the last decades, MRI hardware has developed considerably, showing an increase in main magnetic field strength and improved coil design (e.g., number of receiver coils).…”
Section: Introductionmentioning
confidence: 99%